Stability analysis of unbonded fiber reinforced isolators of square shape. (15th October 2021) - Galano, Simone; Losanno, Daniele; Calabrese, Andrea
Highlights: A large number of finite element analysis of unbounded fiber-reinforced elastomeric isolators (U-FREIs) were carried out by varying mechanical and geometric parameters of the bearings. The behavior of the U-FREIs under simultaneous vertical and horizontal load has been thoroughly investigated. Comparisons between numerical results and analytical formulations from literature is proposed. Stability charts are proposed in order to define the critical pressure as well as the maximum stable horizontal displacement for a given bearing. Abstract: Fiber-reinforced elastomeric isolators (FREIs) are generally installed in unbonded configurations. Because of the simultaneous application of axial loads and large lateral deformations, instability of these bearings is a major concern. This paper shows the results of a large series of 3D finite element analyses (FEAs) on square-shaped FREIs. The analyses aimed at obtaining easy to use design charts where the stability limits of these devices can be rapidly determined. The output of the analyses is compared to analytical results available in literature and the limitations of well-known closed form solutions are discussed.